NEW DATA ON THE LOWER PLEISTOCENE (GELASIAN) LIGNITE BEDS OF CASTEL SAN PIETRO (RIETI, CENTRAL ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
A multiproxy study of the lignite-bearing lacustrine sequence cropping out at Castel San Pietro (CSP) (Rieti, central Italy) provides new insights on the paleoenvironmental evolution of an extensional basin, located on the Tyrrhenian side of the Apennine range. The CSP fossiliferous levels reflect deposition in a stable lacustrine environment. Mammal remains collected from this locality during the past centuries include Stephanorhinus etruscus, Anancus arvernensis and the beaver Castor fiber. The co-existence of the Etruscan rhinoceros and the mastodont suggests a middle Villafranchian age (Montopoli or Coste San Giacomo Faunal Unit) for the lignite beds of CSP. New paleoflora findings are in agreement with an attribution to the Piacenzian or Gelasian age for these deposits whilst the presence of the ostracod Qinghaicypris cf. Q. riojensis suggests a time interval from Zanclean to Gelasian (between ~4.5 and ~1.8 Ma). Accordingly, the lignite beds of CSP most likely were deposited during the Gelasian (from ca. 2.5 to 1.8 Ma; from Montopoli to Coste San Giacomo FUs or possibly to Olivola FU) in forested area and warm and humid conditions.